Global Lipschitz Stability in an Inverse Problem for the Non-stationary Transport Equation - 马晨明 商亮宇 (东华大学学报（英文版）, 2013)
An inverse problem of determining the source term of the non-stationary transport equation was considered. The extra lateral boundary condition was chosen as the observation data. Based on a Carleman estimate on the non-stationary transport equation, a global Lipschitz stability for the inverse problem was proved.